Peran Personal Selling Dalam Mempertahankan Penjualan Smartphone Samsung Di Madura Pada Masa Pandemi Covid-19 (Studi Pada Samsung Excellent Partner Di Madura) - Meita Taurima Prinanti; Yustina Chrismardani (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This research aims to identify and explore the application of the role of personal selling in maintaining sales of Samsung SEP Madura during the COVID-19 pandemi. This type of research uses qualitative research methods with a qualitative descriptive approach. The subjects in this study are RSMO Madura, TL Pamekasan, SEC SEP Pamekasan, TL Bangkalan and SEC SEP Bangkalan. The data collection technique used in this study was to make observations, interviews and documentation. The data analysis technique was done by reducing the data, presenting the data and then drawing conclusions. The results of this study show that there are many changes in adapting to a pandemi by Samsung personal selling, either to increase sell out or increase sell in, with the aim of improving the growth of Samsung Madura.